2018
DOI: 10.1123/japa.2017-0166
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of Factors Influencing Seniors’ Participation in Strength Training in Gyms and Fitness Centers

Abstract: Older people are less likely to engage in strength training than their younger counterparts, despite the substantial benefits of this form of exercise for preventing and addressing age-related physical decline. In many countries, strength training programs are available for older people yet are undersubscribed. The aim of this study was to identify the factors influencing older people's participation in strength training at gyms and fitness centers to provide insights into potentially effective recruitment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Objectively and subjectively assessed Self-rated health, health status, and the presence of depressive symptomatology were negatively related to the amount of time spent in MVPA in the present study. Poor physical and mental health have previously been identified as a barrier to physical activity engagement in both quantitative and qualitative studies with older adults (Baert et al, 2011;Bauman et al, 2012;Burton et al, 2017;Pettigrew et al, 2017 (Liu & Latham, 2011), cardio-metabolic health (Sagar et al, 2015;Yang, Scott, Mao, Tang, & Farmer, 2014), pain associated with osteoarthritis (Fransen, McConnell, Hernandez-Molina, & Reichenbach, 2014), depression (Singh et al, 2005, and cognitive function (Gates, Singh, Sachdev, & Valenzuela, 2013). Given these potential health benefits for older people in poorer health, appropriate exercise programs catering to older adults with limitations should be made available and promoted to older people across a range of health status levels (Bauman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Objectively and subjectively assessed Self-rated health, health status, and the presence of depressive symptomatology were negatively related to the amount of time spent in MVPA in the present study. Poor physical and mental health have previously been identified as a barrier to physical activity engagement in both quantitative and qualitative studies with older adults (Baert et al, 2011;Bauman et al, 2012;Burton et al, 2017;Pettigrew et al, 2017 (Liu & Latham, 2011), cardio-metabolic health (Sagar et al, 2015;Yang, Scott, Mao, Tang, & Farmer, 2014), pain associated with osteoarthritis (Fransen, McConnell, Hernandez-Molina, & Reichenbach, 2014), depression (Singh et al, 2005, and cognitive function (Gates, Singh, Sachdev, & Valenzuela, 2013). Given these potential health benefits for older people in poorer health, appropriate exercise programs catering to older adults with limitations should be made available and promoted to older people across a range of health status levels (Bauman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Study participants reported different motivations for exercising: older men focused on improving their performance and preventing diseases, while older women wanted to maintain mental and physical fitness for their own well-being (to do “something for themselves”). Empirical research on gender-specific motivation for physical activity is still deficient and includes open questions (e.g., [ 29 , 30 ]); however, for both genders, social interaction as well as enjoyment of the activity appear to be greater motivators than performance goals, when compared with younger age groups [ 31 , 32 ]. Programs to promote physical activity should address both motivations, offer a pleasant atmosphere, create individual health benefits, and provide opportunities for social exchange [ 29 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, and in line with existing knowledge, participants stated several important issues when choosing a fitness centre, such as locations with easy access [ 32 – 34 ] clean and well-maintained settings with a variety of up-to-date equipment [ 35 , 36 ] and a centre not too crowded [ 37 ], noisy or smelly [ 38 ]. When participants evaluated the settings, it all came down to how the space affected them; how it made them feel.…”
Section: Discussionmentioning
confidence: 99%